2020
DOI: 10.36565/jab.v9i2.273
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Faktor-Faktor yang mempengaruhi Ambulasi Dini Post ORIF pada Pasien Fraktur Femur Study Retrospektif

Abstract: Femur fracture is a loss of continuity of the femur, which can be caused by direct trauma to the thigh or pathological factors. The main treatment for fractures is ORIF. Implementation of early ambulation is important to prevent post ORIF complications. Objective: This study aims to analyze the factors that influence early ambulation post ORIF  in femoral fracture patients. Methods: The study design was a cross-sectional retrospective approach with 82 respondents and data collection using medical record data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
1
0
3
Order By: Relevance
“…At the time of the fracture, there will be a change in the structure of the bone due to damage, which can result in impaired function of the limbs and cause pain in the area that has a fracture, because of this a person can experience barriers to physical mobility (Wantoro et al, 2020). This is consistent with the results of research conducted by Purba, et al (2021) which showed that the level of pain before ROM exercises was moderate pain (Purba1 et al, 2021).…”
Section: Results and Discussmentioning
confidence: 99%
“…At the time of the fracture, there will be a change in the structure of the bone due to damage, which can result in impaired function of the limbs and cause pain in the area that has a fracture, because of this a person can experience barriers to physical mobility (Wantoro et al, 2020). This is consistent with the results of research conducted by Purba, et al (2021) which showed that the level of pain before ROM exercises was moderate pain (Purba1 et al, 2021).…”
Section: Results and Discussmentioning
confidence: 99%
“…Menurut Wantoro et al, (2020) jenis kelamin laki-laki memiliki sifat lwbih naïf dibandingkan perempuan dimana kecelakaan lalulintas lebih banyak terjadi pada lakilaki dibandingkan perempuan, sehingga laki-laki sering terjadi patah tulang, belum lagi resiko kerja yang berat dan berhubungan dengan keadaan ekstrim. Berdasarkan usia, seorang anak akan berbeda tingkat kemampuan menahan rasa nyerinya dibandingkan dengan seorang remaja.…”
Section: Pembahasanunclassified
“…Komponen pertanyaan yang cukup banyak mengalami peningkatan yaitu tentang cara mobilisasi dini pasca operasi, sesudah diberikan edukasi pasien menjadi tahu bagaimana cara melakukan mobilisasi dini pasca operasi. mobilisasi dini merupakan faktor penting yang dilakukan untuk memperbaiki sirkulasi, mencegah terjadinya masalah serta komplikasi setelah operasi dan dapat mempercepat proses pemulihan, pasien biasanya tidak melakukan mobilisasi dini disebabkan pasien tidak tahu mengenai mobilisasi dini pasca operasi dikarenakan sebelumnya pasien tidak pernah atau kurang mendapatkan informasi dan edukasi mengenai mobilisasi dini (Wantoro et al, 2020) .…”
Section: Tingkat Pengetahuan Sesudah Pemberian Edukasi Mobilisasi Pad...unclassified